(untitled) (Revista Internacional de Folkcomunicação, 2025)
This article examines Benedita Pinto, known as Mãe Bena, leader of the Terreiro São Sebastião in Parintins (AM), as a folk-communication agent and analyzes how her agency is shaped by gender. Folk communication is mobilized to understand the terreiro as a space of symbolic mediation in which meanings circulate through orality, performance, ritual, and hospitality. In dialogue with Black feminist thought, the article argues that Black women’s leadership structures networks of care, memory, and knowledge transmission, and that practices such as chanting, healing rites, food sharing, and spiritual counseling configure communicative languages that confront religious racism. The study is grounded in participant observation during festivals, prayers, and consultations, articulating descriptive analysis and theoretical interpretation. The results indicate that, by translating ritual codes for diverse publics and regulating the tempos of the sacred, Mãe Bena exemplifies the figure of the folk agent, while female protagonism organizes collective life and updates Afro-Indigenous ancestries. It concludes that the terreiro functions as a matrix of cultural resistance and a non-hegemonic communication system in which Mãe Bena’s agency integrates communication, care, and everyday politics in Parintins.